Fast quantification of water in single living cells by near-infrared microscopy - KOPF, ILONA (Royal Society of Chemistry, 2004)
We have set up a near-infrared microscope using a tuneable diode laser in the range from 1530 to 1570 nm. This spectral range is close to the peak of the water overtone absorption. We used this new microscope to study liver cells, hepatocytes, showing that quantitative information of the intracellular water concentration in living cells can be extracted.
PUBLISHED
Keywords: Chemistry; hepatocytes